2018
DOI: 10.18549/pharmpract.2018.04.1298
|View full text |Cite
|
Sign up to set email alerts
|

Swedish patients’ trust in the bioequivalence of interchangeable generics. What factors are important for low trust?

Abstract: Background:Generic substitution (GS), is a cost-containment strategy meant to contain pharmaceutical expenditure without compromising health objectives. In order to shape GS into a policy that is both efficient and safe it is crucial to understand which factors are most important for patients’ trust in GS.Objective:To assess Swedish patients’ level of trust in the bioequivalence of cheap and expensive generic medicines, and the association between trust and various factors.Methods:A cross-sectional study was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 39 publications
2
12
0
3
Order By: Relevance
“…There was also an association between a negative attitude towards generics and being able to match a maximum of two active substances with the correct brand. The results on attitudes in this study are in line with results from studies on generic prescription drugs [ 16 , 19 21 ]. A systematic review of studies from a wide range of countries showed that about one third of the general population hold negative views of generic drugs [ 19 ], a finding which coincides with a review restricted to studies from high-income countries [ 20 ] and the before-mentioned Swedish study [ 16 ].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…There was also an association between a negative attitude towards generics and being able to match a maximum of two active substances with the correct brand. The results on attitudes in this study are in line with results from studies on generic prescription drugs [ 16 , 19 21 ]. A systematic review of studies from a wide range of countries showed that about one third of the general population hold negative views of generic drugs [ 19 ], a finding which coincides with a review restricted to studies from high-income countries [ 20 ] and the before-mentioned Swedish study [ 16 ].…”
Section: Discussionsupporting
confidence: 89%
“…The results on attitudes in this study are in line with results from studies on generic prescription drugs [ 16 , 19 21 ]. A systematic review of studies from a wide range of countries showed that about one third of the general population hold negative views of generic drugs [ 19 ], a finding which coincides with a review restricted to studies from high-income countries [ 20 ] and the before-mentioned Swedish study [ 16 ]. Possible explanations for the negative attitudes towards generics are the common lay belief that lower prices imply poorer quality and the familiarity and trust people tend to have in well-known brands [ 21 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Çalışmada, biyoeşdeğer ilaçlara güveni etkileyen 4 faktör; kadın cinsiyet, ilacın ticari isim ve görünümündeki değişikliklerin ilaca uyumu zorlaştırması, biyoeşdeğer ilaçların birey veya devlet ekonomisine katkı sağlamamaları gibi faktörler saptanmıştır. 24 Ayrıca, Finlandiya'da biyoeşdeğer ilaçların daha sık kullanılması ile ilgili yasal düzenleme sonrasında, hekimlerin bu ilaçlara bakış açısını değerlendirmek için yapılan ankette hekimlerin yarısının etkililik ve güvenlilik ile ilgili kaygılarının olduğu bildirilmiştir. 25 Bernard Lown'un, "Kelimeler, bir doktorun sahip olduğu en güçlü araçtır, ancak iki tarafı keskin bir kılıç gibidir."…”
Section: Kli̇ni̇k Prati̇kte Nosebo Etki̇si̇unclassified